The impacts of the COVID-19 outbreak on the education sector - Haider, S. A.; Gul, A.; Anwar, B.; Tehseen, Shehnaz *; Iqbald, S. (IGI Global, 2021)
The COVID-19 outbreak has prevented students from contributing towards the economic growth of Pakistan. It first disrupted the education system in China and later entered Pakistan to close all levels of educational institutions/sectors since the middle of March 2020. This study aims to highlight the COVID-19 outbreak’s effects on educational sector in Pakistan. Pakistan’s overall public sector expenditure as a percentage of GDP before the pandemic was already low as compared to regional level, but due to the pandemic, it has dropped down significantly. This study seeks to answer two important questions: (1) What are the impacts of COVID-19 outbreak on Pakistan? (2) Will the closure of educational institutions impact the economic growth of Pakistan? According to empirical and theoretical findings, the results show that the lack of school education for a long period of time will contribute towards unskilled human capital. The COVID-19 outbreak has impacted student learning activities, which may increase the dropout rates, loss of mental health, and consequently, may impact the economic growth of Pakistan later.